Thailland / Vietnam / Tibet / India / Jordan / Turkey (St. Laurent, Quebec : Madacy Entertainment : Distributed by Madacy Home Video, 2009)
"Each episode provides a thrilling and informative introduction to an important place on the globe. Placing equal emphasis upon in-depth cultural history and breathtaking aerial cinematography, this series touches upon every inhabited continent--from Turkey to New Zealand. Along the way, you'll visit ancient ruins, marvel at natural phenomena, and discover the infinitely diverse ways that human beings have found to make themselves at home upon the Earth"--Container.
Disc 3 Thailland -- Vietnam -- Tibet -- India -- Jordan -- Turkey --
Originally produced in 1999.
Narrator, Mike Rowe.
DVD ; Dolby digital ; 2.0 Dolby stereo.
Keywords: International travel; Historic sites -- Description and travel; World Heritage areas -- Description and travel; World history; Travelogues (Television programs); Documentary television programs; Nonfiction television programs